Familial congenital peripheral facial paralysis - Portillo Vallenas, Roberto (2001)
Objective: To study 29 individuals belonging to four familiar generations in whom 9 cases of facial paralysis was found in 2 generations. Setting: Neurophysiology Service, Guillermo Almenara Irigoyen National Hospital. Material and Methods: Neurological exam and electrophysiologic (EMG and VCN), otorrhinolaryngologic, radiologic, electroencephalographic, dermatoglyphic and laboratory studies were performed in 7 of the 9 patients (5 men and 2 women). Results: One case of right peripheral facial paralysis in the second generation and 6 cases of left peripheral facial paralysis in the third generation were found, all associated to prolonged congenital enuresis. Conclusions: Study of the 29 persons pedigree determined that 9 of them had hereditary familiar peripheral facial neuropathy, probably dominant type with reduced penetrance.